A Study On E-purchase Decision By Malaysian Consumers - Ashtari, Mohammad (2009)
This study concerns the factors that define the e-purchase behavior of consumers and chooses a general or holistic lens to view and investigate the e-purchase decision by Malaysian consumers mainly towards purchasing of consumer electronic goods because according to some researcher product type plays an important role in consumers' purchase behavior.